Polymorphism of GH/HaeIII and GDF9/AsplEI genes, genetic variation and association of their genotypes with immune status in sheep of different breeds ranched in different natural and geographic areas - A. A. Ozdemirov; A. I. Surov; E. S. Surzhikova; A. A. Khozhokov; Z. K. Gadzhiev; D. D. Evlagina; E. M. Alieva; R. A. Akaeva (Юг России: экология, развитие, 2022)
Aim. One of the important tasks in solving the problem of improving the efficiency of sheep breeding is the rational use of fodder lands in the North Caucasus and the South of Russia, a significant part of which is located in different natural and climatic conditions. The complexity of solutions lies in insufficient knowledge of the mechanisms of adaptation of farm animals, in particular sheep, to the ecological and geographical features of these regions. The  purpose  of  this  research  was  to  study  the  genetic  polymorphism  of genes, the degree of genetic variability and immune status in sheep of different breeds, since genetic polymorphism is a measure of its adaptability and the hematopoietic function of blood is the basis of the life of the organism.Material and Methods. The genetic structure of the GH/Hae III, GDF9/AsplEI genes and immune status, was studied by the methods of genetic‐statistical and immune analysis in sheep of different breeds kept in different climatic zones of Dagestan and the Krasnodar Territory.Results. As a result of DNA genotyping of the studied samples of sheep of different breeds, it was found that polymorphism of GH/HaeIII, GDF9/AsplEI genes is represented by three genotype variants: homozygous GH/HaeIIIАА, GH/HaeIIIВВ;    GDF9/AsplEIАА,    GDF9/AsplEIGG;    heterozygous    GH/HaeIIIAB; GDF9/AsplEIAG  and two alleles: A and B – of the GH/HaeIII gene; A and G – GDF9/AsplEI gene with different frequency of occurrence, respectively.Conclusion. For the first time,  genetic variability has been studied in the context of the immune status of sheep populations of different breeds bred in the foothills of the Republic of Dagestan and Krasnodar Territory. The information obtained about the role of the degree of genetic variability and the immune status of sheep of different breeds is answered in the formation of adaptive‐compensatory mechanisms to specific conditions of the breeding environment.  A  deeper  study  of  the  adaptive  characteristics  of  sheep  of different breeds for their further improvement allows the use of molecular genetic and hematological methods.